Mapiranje in analiza tematskega polja zgodovine v štirih znanstvenih revijah med leti 2009 in 2021 s poudarkom na povezanosti z antropologijo - Naterer, Andrej (Annales. Series historia et sociologia, 2022)
This article examines the integration of anthropology in Slovenian history over the last decade. It is based on an analysis of 1,707 papers published between 2009 and 2021 in four representative history journals, Studia Historica Slovenica, Zgodovinski časopis, Acta Histriae and Annales, Series Historia et Sociologia. A content analysis of papers reveals the integration of the field of history and analyzes the embedding of anthropological content in Slovenian history. The results show (1) that there are 18 distinctive thematic areas in Slovenian history research in the sample under consideration, (2) that the topics can be categorized into 4 groups: (a) National topics (b) Military topics, (c) Local topics and (d) Church-biographical themes, (3) that the presence and relationships between the central themes appears to be uniform from 2009, (4) that the field appears to be strongly masculinized, (5) that history has a strong basis in the humanities, (6) that the themes show a relatively limited range, and (7) that anthropology comprises an integral part of the study of Slovenian history.
Keywords: anthropology; antropologija; bibliometrija; content analyses; history; thematic mapping; zgodovina; znanstveni časopisi